Laryngectomy Complications Are Associated with Perioperative Antibiotic Choice. (5th May 2015) - Langerman, Alexander; Ham, Sandra A.; Pisano, Jennifer; Pariser, Joseph; Hohmann, Samuel F.; Meltzer, David O.
Abstract : Objective: To assess hospital‐ and physician‐level variation in pattern of perioperative antibiotic use for laryngectomy and the relationship between pattern of antibiotic use and surgical site infection (SSI), wound dehiscence, and antibiotic‐induced complications. Study Design: Retrospective analysis of University HealthSystem Consortium data. Setting: Academic medical centers and affiliated hospitals. Subjects and Methods: Elective admissions for laryngectomy from 2008 to 2011 and associated 30‐day readmissions were analyzed with multivariate logistic regression models. Results: There were 439 unique antibiotic regimens (agents and duration) identified over the first 4 days of the 1865 admissions included in this study. Ampicillin/sulbactam, cefazolin + metronidazole, and clindamycin were the most common agents given on the day of surgery. Clindamycin was independently associated with higher odds of SSI (odds ratio [OR] = 3.87, 95% confidence interval [CI] = 2.31‐6.49]), wound dehiscence (OR = 3.42, 95% CI = 2.07‐5.64), and antibiotic‐induced complications (OR = 3.01, 95% CI = 1.59‐5.67) when given alone; it was also associated with higher odds of SSI (OR = 2.69, 95% CI = 1.43‐5.05) and antibiotic‐induced complications (OR = 2.20, 95% CI = 1.04‐4.64) when given with other agents. These effects were stronger in a subsample of high‐volume physicians and hospitals. Conclusion: There is substantial variability in perioperative antibiotic strategies for laryngectomy. Clindamycin was associated with much higher odds of short‐term complications as compared to other common regimens. Based on these data, clinical trials should be planned to firmly establish the most effective and cost‐effective antibiotic management for laryngectomy and determine potential alternatives to clindamycin for penicillin‐allergic patients.